Towards A Dynamic Model of Human Needs: A Critical Analysis of Maslow's Hierarchy - Ghaleb, Belal Dahiam Saif (PT. Riset Press International, 2024)
This paper critically analyzed Abraham Maslow's well-known hierarchy of needs theory (1943), identified its shortcomings, and examined previous studies in the literature on qualitative research methods. Moreover, it discussed the suitability of the theory to human needs and its scientific nature, considering the qualifications, dynamics, variability, and nature of human needs. Maslow proposed a rigid hierarchical framework, categorizing human needs from physiological to self-actualization. Over time, the theory faced criticism for disregarding scientific principles and overlooking the objective and subjective aspects of human needs. Instead of rigorous scientific research, the theory heavily relied on Maslow's personal observations and clinical experiences. This paper posits that Maslow overlooked socio-cultural influences that shape motivation and emphasizes how social and economic contexts prioritize needs. Moreover, the lack of empirical evidence is identified as a weakness compromising the theory's validity. The article also, proposes an updated framework considering the objectivity and subjectivity of human needs, scientific research principles, technological connections, sustainability, socio-cultural influences, arbitrary human behavior and needs, personal preferences, and emotional factors. It advocates for acknowledging that needs circulate dynamically through interpersonal networks rather than being staged rigidly, thereby supporting theoretical evolution. Additionally, the paper identifies and offers potential solutions to eight fundamental issues associated with the theory. In this study, a literature review was conducted, and Maslow's hierarchy of needs was analyzed and its deficiencies were identified and eliminated. Igor Kospov's model was examined and explained to eliminate its flaws. Finally, instead of Maslow's hierarchy of needs, the article proposes a model or set of clustered needs that are compatible with human needs and scientific, dynamic, interactive, prioritized by humans, and influenced and influenced by culture, technological developments and the human environment. The model, or clustered set of needs, consists of several clusters. These clusters are interconnected and influence each other. In other words, the same person can take steps towards self-actualization and experience the indispensable feature of social belonging while he satisfies the physiological needs of drinking water and eating, because human needs can vary from person to person, from place to place, from time to time and from situation to situation, even within the same person.